The adequacy of MyDRP in dealing with cybersquatters in Malaysia / Irianie Abdul Wahab - Abdul Wahab, Irianie (2005)
The issue of cyber squatting in Malaysia is relatively new. To date, there is no law to govern the problems of cyber squatting. The aim of this dissertation is to highlight the inadequacy of the alternative dispute resolution (ADR) namely MyDRP as an administrative mechanism to prevent cyber squatting. This paper examines the policy and rules concerning domain name dispute in Malaysia and cross-referencing them to certain decisions decided under the same method. Here, countries such as the UK and the USA will be discussed in greater detail as to provide different approaches to deal with cyber squatting. However, another mechanism which is the legislative approach is compared to that of ADRs. A comparative study is made between the USA and the UK, where most reported litigation has taken place and where the decided cases have persuasive authority on the development of Malaysian Law.